2021
DOI: 10.3390/vaccines9090975
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the Cluster A and V1V2 Targets into a Minimal Structural Unit of the HIV-1 Envelope to Elicit a Cross-Clade Response with Potent Fc-Effector Functions

Abstract: The generation of a potent vaccine for the prevention and/or control of HIV-1 has been unsuccessful to date, despite decades of research. Existing evidence from both infected individuals and clinical trials support a role for non-neutralizing or weakly neutralizing antibodies with potent Fc-effector functions in the prevention and control of HIV-1 infection. Vaccination strategies that induce such antibodies have proven partially successful in preventing HIV-1 infection. This is largely thought to be due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Moreover, we found that patients with anti‐E2 antibodies targeting Domain B and D that are known to be associated with effective neutralization 55–59 are also the ones that had antibodies strongly associated with high ADCP, further supporting the notion that there may be overlapping protective functions via dually acting antibodies. This is consistent with reports on HIV in which overlapping ADCP and neutralizing functions were observed, 24 and antibodies that maintain broad neutralization function against several HIV variants also possessed potent Fc receptor‐dependent effector functions including ADCP 14,17,24,25 . However, future studies aimed at defining the significance of ADCP in HCV, namely its role in viral clearance and clinical outcomes using live viruses, is warranted.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, we found that patients with anti‐E2 antibodies targeting Domain B and D that are known to be associated with effective neutralization 55–59 are also the ones that had antibodies strongly associated with high ADCP, further supporting the notion that there may be overlapping protective functions via dually acting antibodies. This is consistent with reports on HIV in which overlapping ADCP and neutralizing functions were observed, 24 and antibodies that maintain broad neutralization function against several HIV variants also possessed potent Fc receptor‐dependent effector functions including ADCP 14,17,24,25 . However, future studies aimed at defining the significance of ADCP in HCV, namely its role in viral clearance and clinical outcomes using live viruses, is warranted.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with reports on HIV in which overlapping ADCP and neutralizing functions were observed, 24 and antibodies that maintain broad neutralization function against several HIV variants also possessed potent Fc receptor‐dependent effector functions including ADCP. 14 , 17 , 24 , 25 However, future studies aimed at defining the significance of ADCP in HCV, namely its role in viral clearance and clinical outcomes using live viruses, is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding capacity of the purified ACE2-Fcs to various viral antigens was measured by indirect ELISA, as described in ( 61 ). Ninety-six–well Nunc Maxisorp plates (Sigma-Aldrich) were coated with SARS-CoV-2 RBD wt (residues 319 to 541) (50 ng), RBD B.1.351 (50 ng), S-2P (75 ng), S B.1.1.7 (75 ng), S B.1.351 (75 ng), S P.1 (75 ng), S B.1.526 (75 ng), and SARS-CoV-1 RBD (50 ng) per well in tris-buffered saline (TBS) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that the release of sgp120 from infected cells sensitizes uninfected bystander CD4 + T cells to ADCC mediated by HIV+ plasma in vitro, whether this happens in PLWH remains unclear [15][16][17]. We therefore measured the levels of anti-cluster A antibodies using an engineered stabilized gp120 inner domain protein (ID2) only exposing the cluster A region [24,31]. Figure 2 and Table S1, present the associations between anti-cluster A antibodies and absolute CD4 cell counts or the CD4:CD8 ratio (Figure S1).…”
Section: Anti-cluster a Antibodies Levels Are Associated With Immune ...mentioning
confidence: 99%